Regular use of aspirin is associated with a lower cardiovascular risk in prostate cancer patients receiving gonadotropin-releasing hormone therapy - Chang, Wei-Ting; Hong, Chon-Seng; Hsieh, Kun-Lin; Chen, Yi-Chen; Ho, Chung−Han; Shih, Jhih-Yuan; Kan, Wei-Chih; Chen, Zhih-Cherng; Lin, You-Cheng (Frontiers in Oncology, 2022)
Gonadotropin-releasing hormone (GnRH) therapy has been known to increase risks of major adverse cardiovascular and cerebrovascular events (MACCEs). Herein, we aim to estimate whether regular use of aspirin attenuates risks of MACCEs in prostate cancer patients receiving GnRHs. Using Taiwanese National Health Insurance Research Database (NHIRD), we identified 7719 patients diagnosed with prostate cancer who were either aspirin-naïve, received irregular or regular aspirin from 2008 to 2015. Through a multivariable logistic regression model, we investigated the impact of aspirin on MACCEs. Compared with nonusers and irregular users, most patients receiving regular aspirin were older and had more comorbidities. The crude incidence of one-year MACCEs was lowest in aspirin nonusers but highest in irregular users of aspirin compared with regular users of aspirin (2.65% vs. 4.41% vs. 2.85%, p=0.0099). After adjusting for age, cancer stage and comorbidities, irregular aspirin users had a higher risk of one-year MACCEs (adjusted OR: 1.33; 95% CI: 0.93-1.90, p=0.1139) than aspirin nonusers, but conversely, there was a trend of reducing the risk of MACCEs among those who received regular aspirin (adjusted OR: 0.79; 95% CI: 0.44-1.42, p=0.4256). In the subgroup analysis, there were age- and cancer stage-independent higher risks of MACCEs in patients who took aspirin irregularly compared to those in patients who did not take aspirin. The risks were attenuated in patients receiving regular aspirin. Collectively, regular use of aspirin presented a trend of reducing risks of MACCEs in prostate cancer patients receiving GnRHs. However, irregular use of aspirin diminished the benefits.